Cause Analysis and Solution of False Alarm in Coal Mine Safety Monitoring System - Feng , Xuewei (Journal of Theory and Practice of Engineering Science, 2023)
With the continuous development of social economy, coal mining industry has made great progress. In the coal mine safety production, its safety monitoring system is becoming more and more perfect, in the face of a variety of potential accidents, can provide timely warning information to the relevant personnel, to avoid casualties and property losses. But in the actual work of mine safety monitoring system, the phenomenon of false alarm often occurs, which affects the reliability of mine safety monitoring system data. Therefore, this paper mainly analyzes the causes of false alarm in coal mine safety monitoring, and puts forward targeted technical solutions, aiming at improving the accuracy of coal mine safety monitoring data and laying a solid foundation for coal mine safety production.